2021
DOI: 10.1093/jmammal/gyab074
|View full text |Cite
|
Sign up to set email alerts
|

Response of mesocarnivores to anthropogenic landscape intensification: activity patterns and guild temporal interactions

Abstract: Carnivores face important anthropogenic threats in agricultural areas from habitat loss and fragmentation, disturbance by domestic free-roaming dogs and cats, and direct hunting by humans. Anthropogenic disturbances are shifting the activity patterns of wild animals, likely modifying species interactions. We estimated changes in the activity patterns of the mesocarnivore guild of agricultural landscapes of the La Araucanía region in southern Chile in response to land-use intensification, comparing intra- and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 78 publications
1
20
0
1
Order By: Relevance
“…As for the lesser grison treatment, it seems that the threat it posed was not enough to activate the HPA axis. As we mentioned before, lesser grison is scarce in the study area [ 19 ], and they have different active periods ( O. longicaudatus is nocturnal while lesser grisons are mostly diurnal) [ 19 ]. Moreover, studies conducted in other regions showed that O. longicaudatus is not an important part of the lesser grison diet, [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As for the lesser grison treatment, it seems that the threat it posed was not enough to activate the HPA axis. As we mentioned before, lesser grison is scarce in the study area [ 19 ], and they have different active periods ( O. longicaudatus is nocturnal while lesser grisons are mostly diurnal) [ 19 ]. Moreover, studies conducted in other regions showed that O. longicaudatus is not an important part of the lesser grison diet, [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analysed the behavioural and physiological responses of Oligoryzomys longicaudatus to two predators which show different activity patterns, densities and dietary preferences. On the one hand, the culpeo fox seems to be more abundant in the study area [ 19 ] and their daily activity patterns are cathemeral, exhibiting intermittent activity throughout the 24 h cycle [ 19 ]. In other regions, the culpeo fox has been described as a facultative trophic specialist mainly feeding on rodents and lagomorphs, depending on local abundances [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…behavior and activity patterns (Gálvez et al, 2021;Zapata-Ríos & Branch, 2016). For example, bobcats (Felis concolor) became more nocturnal in response to human activity and the presence of dogs (George & Crooks, 2006).…”
Section: Dogs Have Been Shown To Have a Profound Influence On Wildlifementioning
confidence: 99%